1995
DOI: 10.1128/jcm.33.7.1720-1726.1995
|View full text |Cite
|
Sign up to set email alerts
|

Rapid assay for mycobacterial growth and antibiotic susceptibility using gel microdrop encapsulation

Abstract: Effective control of tuberculosis transmission in vulnerable population groups is dependent on rapid identification of the infectious agent and its drug susceptibility. However, the slow growth rate of mycobacteria has undermined the ability to quickly identify antimicrobial resistance. These studies describe a mycobacterial growth assay based on microencapsulation technology used in conjunction with flow cytometric analysis. Mycobacteria were encapsulated in agarose gel microdrops approximately 25 m in diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0

Year Published

1999
1999
2008
2008

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 44 publications
(28 citation statements)
references
References 19 publications
1
27
0
Order By: Relevance
“…Streptomycin consistently achieved a 99% reduction in plaque counts after only a 24-h exposure. This is consistent with data from another mycobacteriophage-based assay, the LRP assay, in which a 99% reduction in the light signal was seen after an overnight incubation of susceptible isolates with streptomycin (16). In the PhaB assay, exposure of cells to isoniazid, ethambutol, pyrazinamide, and ciprofloxacin for 48 h is recommended, which is also consistent with the LRP assay (15).…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Streptomycin consistently achieved a 99% reduction in plaque counts after only a 24-h exposure. This is consistent with data from another mycobacteriophage-based assay, the LRP assay, in which a 99% reduction in the light signal was seen after an overnight incubation of susceptible isolates with streptomycin (16). In the PhaB assay, exposure of cells to isoniazid, ethambutol, pyrazinamide, and ciprofloxacin for 48 h is recommended, which is also consistent with the LRP assay (15).…”
Section: Discussionsupporting
confidence: 86%
“…The Centers for Disease Control and Prevention recommend that all isolates of Mycobacterium tuberculosis be tested for their susceptibility to antibiotics, using the most rapid methods possible, and that susceptibility data for first-line drugs be available within 30 days of receipt of a specimen (18). Conventional culture-based techniques for susceptibility testing take several weeks to complete, and although both radiometric and nonradiometric liquid culture systems have significantly reduced turnaround times, results are still not available for 5 to 12 days after receipt of an isolate (1,16). Rapid phenotypic methods have a potential advantage, in that they can be applied to susceptibility testing of any drug that inhibits the phenotypic marker being studied.…”
mentioning
confidence: 99%
“…A flow cytometer can make sensitive and precise measurements of light scattered or emitted by individual cells at a dozen or more different wavelengths, even though the cell images obtained are typically not in focus. Based on prior experience with both flow and image (105, 106) cytometry, and more recent theoretical (11) and experimental (12) work, we concluded that it should be possible to build a small, robust, energy‐efficient, and extremely inexpensive fluorescence image cytometer that could perform essentially the same measurements now done for TB diagnosis by laser scanning cytometry (72) and automated microscopy (76, 77) and for rapid (24–48 h) antimicrobial susceptibility determination of MTB by flow cytometry (71, 94–104).…”
Section: A Minimalist Fluorescence Image Cytometer For Resource‐poor mentioning
confidence: 98%
“…A series of studies (94–101) published since 1995 by Ronald Schell and his colleagues at the University of Wisconsin established that flow cytometry can be used to determine susceptibility of MTB to all first‐line and several second‐line drugs within 24–36 h; other groups (71, 102–104) have obtained similar results. Reis et al (103) noted that their work was entirely done in a developing country (Brazil).…”
Section: Determination Of Antimicrobial Susceptibility In Tbmentioning
confidence: 99%
“…ES cell aggregates were dispersed in molten 1.5% (weight) low-gellingtemperature agarose (type VII, Sigma, St. Louis, MO) in Dulbecco's phosphate-buffered saline (PBS, GIBCO-BRL, Grand Island, NY) at 2 Â 10 6 cells/mL. The molten agarose mixture was dispensed into 200-centistoke viscosity dimethylpolysiloxane (DMPS, Sigma) at 37jC and subjected to impeller shearing using the CellSys Microdrop Maker (One Cell Systems) to create agarose hydrogel microcapsules (Ryan et al, 1995). Microcapsules were washed twice with Hank's buffered saline solution (HBSS, GIBCO-BRL) and suspended in the appropriate ES cell differentiation media.…”
Section: Encapsulated Suspension Culturesmentioning
confidence: 99%